Le semantique des subordonnants de cause - Bulikowski, Brunon (Wydawnictwo Naukowe UAM, 2003)
This paper deals with the semantic values of grammatical means expressing casual relationships in a sentence. The study focuses on constructions based on the relation of subordination. The author undertakes a typology based on semantic criteria. A large portion of the paper is devoted to the grammatical means simultaneously expressing the cause and the time. The author was inspired by observations made during language classes with French majors.